Localization of redox-hotspots using a comparative tracer tomography approach. (May 2022) - Somogyvári, Márk; Knabe, Dustin; Engelhardt, Irina
Highlights: A comparative tracer tomography approach is introduced. Combined use of reactive and conservative tracers to reveal reactive pathways. The geometry of biogeochemical heterogeneities can be reconstructed. Abstract: The identification of reactive hotspots in shallow porous aquifers is challenging, and normally requires extensive geochemical data collection combined with computationally intensive reactive transport modeling. In this study we propose an alternative, practical approach, combining conservative and reactive tracers using a tomographic setup to localize such zones. Tracer tomography combines multiple tracer tests to capture and reconstruct aquifer heterogeneities. These methods generally use "ideal" tracers that are dominantly transported by conservative advection to provide a hydraulically accurate aquifer reconstruction. We compare these conservative tracer tomography results to those obtained by using reactive tracers in a similar tomographic setup. Assuming that the conservative tracer is ideal, the differences between the two tracers will be mainly related to reactive transport. In natural systems, the biogeochemical reactions happen in localized zones, these will be the parts of the reconstructions with the greatest differences. We present the viability of the approach in a simple 2-D example, and on an aquifer analog model-based complex example. With extensive sensitivity analysis, we test the effectiveness of the method under different reaction intensities to define the chemical requirements for an ideal reactive tracer for such investigations.